Pengukuran Kekuatan Sinyal Receive Strangth Signal Indicator (RSSI) 4.5G VoLTE Provaider Telkomsel di Universitas Mataram: Signal Strength Measurement Receive Strangth Signal Indicator (RSSI) 4.5G VoLTE Provider Telkomsel at the University of Mataram - Made Sutha Yadnya; I. G. P. Wedashwara Wedarama; I Wayan Sudiarta (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2022)
This is an initial study to determine the quality of the 4.5G VoLTE signal in the area around the University of Mataram campus. This is done to get the Receive Strangth Signal Indicator (RSSI) measurement emitted by the Base Transceiver Station (BTS) owned by the Telkomsel provider at FMIPA because the VoLTE signal is unstable. The measurement method used is the drive-test. But the results are not entirely as desired. Because in some places it turns out that the quality of receiving power is very weak. Measurements obtained by drive-test carried out in the morning, afternoon, evening and night, obtained the difference in the average signal, the value of each measurement place so that it can be read more quickly converted from numbers to colors. The measurement results and theory were compared so that the RSSI level at Mataram University was obtained.